Imaging of carbon nanomembranes with helium ion microscopy - Beyer, André; Vieker, Henning; Klett, Robin; Meyer zu Theenhausen, Hanno; Angelova, Polina; Gölzhäuser, Armin (Beilstein Journal of Nanotechnology, 2015)
Carbon nanomembranes (CNMs) prepared from aromatic self-assembled monolayers constitute a recently developed class of 2D materials. They are made by a combination of self-assembly, radiation-induced cross-linking and the detachment of the cross-linked SAM from its substrate. CNMs can be deposited on arbitrary substrates, including holey and perforated ones, as well as on metallic (transmission electron microscopy) grids. Therewith, freestanding membranes with a thickness of 1 nm and macroscopic lateral dimensions can be prepared. Although free-standing CNMs cannot be imaged by light microscopy, charged particle techniques can visualize them. However, CNMs are electrically insulating, which makes them sensitive to charging. We demonstrate that the helium ion microscope (HIM) is a good candidate for imaging freestanding CNMs due to its efficient charge compensation tool. Scanning with a beam of helium ions while recording the emitted secondary electrons generates the HIM images. The advantages of HIM are high resolution, high surface sensitivity and large depth of field. The effects of sample charging, imaging of multilayer CNMs as well as imaging artefacts are discussed.
Keywords: 2D materials; carbon nanomembrane; helium ion microscopy; self-assembled monolayers